Consumer Loss Aversion and Scale-Dependent Psychological Switching Costs - Heiko Karle; Heiner Schumacher; Rune Vølund (Center for Economic Studies and ifo Institute (CESifo), 2021)
We consider the Salop (1979) model of product differentiation and assume that consumers are uncertain about the qualities and prices of firms' products. They can inspect all products at zero cost. A share of consumers is expectation-based loss averse. For these consumers, a purchase plan, which involves buying products of varying quality and price with positive probability, creates disutility from gain-loss sensations. Even at modest degrees of loss aversion they may refrain from inspecting all products and choose an individual default that is strictly dominated in terms of surplus. Firms' strategic behavior exacerbates the scope for this effect. The model generates "scale-dependent psychological switching costs" that increase in the value of the transaction. We find empirical evidence for the predicted association between switching behavior and loss aversion in new survey data.
Keywords: D21; D83; L41; 330; switching costs; competition; loss aversion